Perpaduan Pembelajaran CTL dan GI pada Materi Bentuk Aljabar Untuk Meningkatkan Hasil Belajar Siswa - Masduki, Achmad Imron (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2021)
This study aims to improve student learning outcomes in learning algebraic forms with a combination of the Contextual (CTL) approach with the Group Investigation (GI) model. The type of research used is Classroom Action Assessment (PTK), with research procedures using a cycle model, from the results of the study the percentage of student learning outcomes in Cycle I reached 77% and Cycle II was 100%. This proves that the level of student understanding increases with the application of a combination of the Contextual approach (CTL) with the Group Investigation (GI) model, this combination is used for teaching that can best illustrate with examples of basic illustrations.